The role of agricultural extension workers in digital transformation at the Agricultural Extension Center in Lowokwaru Malang - Salsabella, Irene Hanies; Bakhtiar, Ary; Ibrahim, Jabal Tarik (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: The pivotal role of the agricultural sector in Indonesia's economic advancement stems from the employment of a significant portion of the Indonesian populace. Central to this sector are agricultural extension workers tasked with fostering motivational shifts, altering operational methodologies, and instilling adaptive practices congruent with technological advancements. This research endeavors to scrutinize the modus operandi of agricultural extension workers amidst the digital metamorphosis era within the Agricultural Extension Center situated in Lowokwaru, Malang, Indonesia. Methods: Employing a Mixed methods approach, this study draws upon primary and secondary data sources. Thirty samples, affiliated with the Farmers Group at the Agricultural Extension Center in Lowokwaru Malang, constitute the study cohort, selected through purposive sampling techniques. Data accrual involves questionnaire administration, employing the Likert scale as the measurement metric. Statistical analysis entails multiple linear regression, facilitated through SPSS 22 software. Results: Simultaneously, variables embodying extension workers' roles as facilitators, innovators, motivators, dynamists, and educators collectively impact the income of registered farmers at the Agricultural Extension Center in Lowokwaru, Malang. Conclusion: This study reveals that the roles of extension workers as facilitators, innovators, and educators significantly enhance farmers' capacity to integrate digital technology into their agricultural practices. Nevertheless, the absence of direct statistical significance in some roles suggests the interplay of other critical factors, such as farmers' readiness to adopt technology and external support mechanisms. These findings highlight the need for targeted interventions to bolster extension workers' capabilities and farmer engagement with digital innovations.